Identifikasi Bahaya, Penilaian Risiko Terhadap Keselamatan Kerja Coalgetting Di Tambang Terbuka PT. Bima Putra Abadi Citranusa Lahat, Desa Lubuk Betung, Kecamatan Merapi Selatan, Provinsi Sumatera Selatan. - ANGGA YUJA WIGUNA; Fadhilah Fadhilah; Rusli HAR; Admizal Nazki (Departemen Teknik Pertambangan FT UNP, 2021)
Abstrak. PT. Bima Putra Abadi Citranusa is a subsidiary of the Bomba Group, this company is a domestic mining company engaged in coal mining. PT. BPAC started operations in July 2020 using the open pit mining method. The accident rate at PT. Bima Putra Abadi Citranusa in 2020 were 12 accidents that occurred in September – December 2020. The data collection technique used a work activity questionnaire. The results of data collection that have been obtained from surveys at mining sites will be arranged systematically and can be used as material for analysis in seeing the level of work safety (K3) in the process of mining activities using the HIRARC method. Identification of hazards and risks 38,23% is a hazard condition that has the lowest severity there are 13 conditions contained in the process of mobilizing heavy equipment, the process of transporting coal with DT, the process of dumping in the stock rom, the pump installation process, the process of driving the LV unit. Identification of hazards and risks 35,29% is a hazard condition that has moderate severity there are 12 hazard conditions contained in the process of mobilizing heavy equipment, loading process using excavators, coal hauling process with DT, dumping process in stock rom, pump installation process, process driving the LV unit Identification of hazards and risks 14,70% is a hazard condition that has a significant severity there are 5 hazard conditions contained in the process of transporting coal with DT, the process of driving an lv unit, activities at night activities. Identification of hazards and risks of 11.76% is a hazard condition that has a high severity level, there are 4 conditions contained in the process of loading with an excavator into the DT, the process of transporting coal with the DT, the pump installation process, activities at night. Kata kunci: Coal Mining, Hazard Identification And Safety Risk Assessment, HIRARC, Hazard Potential.